2021
DOI: 10.1111/1365-2435.13903
|View full text |Cite
|
Sign up to set email alerts
|

Tissue chemistry of biocrust species along an aridity gradient and comparison to vascular plant leaves

Abstract: Wright et al., 2004). Carbon, fixed by plants during photosynthesis, forms the basis of all organic molecules within plants and can be strategically allocated to reproductive, growth or defensive functions (Hartmann et al., 2020). Within photosynthetic organisms, nitrogen concentrations are strongly linked to protein construction, particularly rubisco (ribulose-1,5-bisphosphate carboxylaseoxygenase). Similarly, phosphorus can serve as a proxy for ribosome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Rainfall in summer will typically evaporate more rapidly than in cooler seasons, allowing lichens and mosses less time to accrete carbon and offset the costs of desiccation. Carbon balance is thought to be a key driver of lichen and moss range limits in drylands (Mallen‐Cooper & Cornwell, 2021) and there is strong experimental evidence that shorter periods of summer rainfall lead to mortality in mosses as carbon balances become negative (Coe et al, 2012; Reed et al, 2012). As such, greater dryland area in the future does not necessarily correspond to more climatically suitable area for dryland‐adapted lichens and mosses.…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall in summer will typically evaporate more rapidly than in cooler seasons, allowing lichens and mosses less time to accrete carbon and offset the costs of desiccation. Carbon balance is thought to be a key driver of lichen and moss range limits in drylands (Mallen‐Cooper & Cornwell, 2021) and there is strong experimental evidence that shorter periods of summer rainfall lead to mortality in mosses as carbon balances become negative (Coe et al, 2012; Reed et al, 2012). As such, greater dryland area in the future does not necessarily correspond to more climatically suitable area for dryland‐adapted lichens and mosses.…”
Section: Discussionmentioning
confidence: 99%
“…The ratios of C, N, and P might indicate nutrient limitation in cryptogam species growth in biocrusts (Y. Li et al, 2019b). Biocrusts can become C limited due to declining biocrust C:N ratios, often caused by declining C content in drylands soil (Mallen‐Cooper & Cornwell, 2021). In contrast, Xu et al (2021) found that C:N ratios of biocrust systems may indicate N limitation, because N fixed by cyanobacteria could accumulate at higher rates than C, reducing C:N ratios.…”
Section: Discussionmentioning
confidence: 92%
“…These factors could explain the better response of plants in soils amended with sewage sludge compost than with organic solid waste compost. However, biocrusts differ from plants in that they are principal players in increasing major soil P and N pools, and their growth is more likely limited by C due to restrictions to photosynthesis (Mallen‐Cooper & Cornwell 2021). Indeed, we observed positive effects of biocrust increasing P and ammonium concentration in the experimental units, in accordance with their role in soil fertility (Belnap 2011; Elbert et al 2012).…”
Section: Discussionmentioning
confidence: 99%